Doing public good? private actors, evaluation, and public value - Guerrero O., R. Pablo; Rist, Ray C. 1944-; Wilkins, Peter 1961- (Transaction Publishers, 2016)
The provision and evaluation of public services by non-public actors : concepts and questions / Andrew Gray -- Three models of doing good : recognizing the implications of delivering behavior change and system transformation / Tom Ling -- Philanthropy, the state and public goods / Tobias Jung and Jenny Harrow -- Accountability for the public policy contribution of not-for-profit organizations : who is accountable to whom, and for what?" / Peter Wilkins and David Gilchrist -- Achieving results for private actors in Africa / Per Oyvind Bastoe and Elizabeth M. White -- The rise of indigenous African foundations/philanthropies and their development impact / Andrew O. Asibey -- How accountable are charitable organizations : an empirical study of international children's aid organizations / David Kirsch and Robert Schwartz -- The provision of public goods and services by social oriented entrepreneurs experiences of Indian healthcare / Andrew Gray and Rosalind Miller -- The social impact bond : the role of evaluation / David Gilchrist and Peter Wilkins -- Being good, but doing good? : the Conrad N. Hilton Foundation's role in the provision of safe water supply in Africa / R. Pablo Guerrero O -- Reframing "doing good" : a Canadian case study / Pearl Eliadis -- Conclusions / Donald Lemaire.
Keywords: Non-governmental organizations / Evaluation / Developing countries; Economic assistance / Evaluation / Developing countries; Technical assistance / Evaluation / Developing countries; Social service / Evaluation / Developing countries; Non-governmental organizations; Developing countries; Evaluation; Economic assistance; Developing countries; Evaluation; Technical assistance; Developing countries; Evaluation; Social service; Developing countries; Evaluation